A fast MPPT technique based on I-V curve characteristics under partial shading - Jubaer, Ahmed; Zainal, Salam; Then, Yi Lung; Saad, Kashem (2017)
This paper has proposed a new MPPT scheme to speed up the global peak searching process under partial shading. In this scheme, characteristics of I-V curve is critically analyzed to design an intelligent mechanism. Through that, several sections of the curve can be easily avoided from scanning as there is no chance of having a local peak. Consequently, MPPT scanning under partial shading become guided and faster to detect the global peak. The MPPT algorithm is simulated in Matlab Simulink where PV array is implemented adjunct with a buck-boost converter. Several tests are carried out with multiple peaks based partial shading curves using the proposed scheme, adaptive P&O and PSO. In comparison of tracking, the proposed scheme outperforms the other two by significant margin. Depending on the cases, proposed method has speeded up the searching process by 2-3 times than adaptive P&O and PSO. Besides, in all cases the MPPT efficiency is well maintained above 99.8%.